Association of streptococcal throat infection with plaque psoriasis - Bhuiyan, Mohammed Saiful Islam; Sultana, Abida; Rabin, Farzana; Haque, AKM Rejaul; Zakaria, ASM (Bangladesh Medical Journal, 2016)
The association of streptococcal sore throat with guttate psoriasis is well established, but its association with psoriasis vulgaris is not yet clear. This cross-sectional observational study was conducted in the department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from June, 2012 to February 2013 with the intention to ascertain whether streptococcal throat infections are more common in patients with chronic plaque psoriasis. Antistreptolysin O (ASO) titre and culture for ?-haemolytic streptococci was done among thirty four patients with chronic plaque type psoriasis and same number of normal healthy controls. Raised ASO titre was found in 26.5% of patients with psoriasis vulgaris and 11.8% of normal healthy controls (p>0.05). Culture of throat swab for streptococcus ?-haemolyticus was positive in 20.6% of psoriatics and none of controls. Laboratory evidences of streptococcal throat infection are more common in patients with chronic plaque type psoriasis. More clinical trials to see the e_cacy of anti-streptococcal therapy and tonsillectomy in plaque psoriasis should be carried out. Bangladesh Med J. 2015 May; 44 (2): 102-104